Spatial and temporal analysis of the risks posed by total petroleum hydrocarbon and trace element contaminants in coastal waters of Kuwait. Issue 1 (15th July 2017) - Nicolaus, E.E.M.; Wright, S.R.; Barry, J.; Bolam, T.P.C.; Ghareeb, K.; Ghaloom, M.; Al-Kanderi, N.; Harley, B.F.M.; Le Quesne, W.J.F.; Devlin, M.J.; Lyons, B.P.
Abstract: Nine trace elements including As, Cd, Cu, Fe, Hg, Ni, Pb, V and Zn, and total petroleum hydrocarbons were analysed from water samples collected from 23 stations since 1984 from Kuwaiti coastal waters. Here it was investigated whether concentrations of these determinants are at levels above Kuwaiti and internationally established assessment criteria (AC). The results indicate that Cu and Cd had the most Kuwaiti AC breaches over time. Comparing the data of the last sampled year to the least stringent international AC, then Cu and Cd showed breaches at all stations. The trends for trace metals are significantly downwards, especially for Cd and Hg. No determinant measured showed a significant upward trend, indicating that water pollution for these contaminants is not a worsening situation. However, further sampling should be carried out to confirm these findings, especially at shoreline locations, where routine monitoring ceased in 2011 to investigate any recent changes. Highlights: Analysis of 9 trace elements and TPHs in Kuwaiti waters indicated Cu and Cd breached most Kuwaiti ACs over time Cu and Cd still breach least stringent international ACs in last sampled year The trends for trace elements are significantly downwards in Kuwaiti coastal waters No sampled determinant showed a significant increase Further sampling at shoreline stations is recommended as it ceased in 2011